Terapia robótica en pacientes con accidente cerebrovascular. - Rojas Cargua, Marco Alexis (2025)
Introduction: Stroke is a neurological condition caused by the interruption of blood flow to the brain, resulting in potential permanent or temporary deficits. It often leads to significant disability, affecting motor, sensory, and cognitive functions, and increases the risk of dependency and falls. Effective rehabilitation, including robotic therapy, is essential for promoting recovery and enhancing brain function. Objective: This study aims to assess the impact of robotic therapy on neurorehabilitation outcomes in stroke patients. Methodology: A bibliographical approach was employed, with articles selected from PubMed, Scopus, and PEDro based on predefined inclusion and exclusion criteria. Results: A total of 25 scientific articles were reviewed and evaluated using the Physiotherapy Evidence Database (PEDro) scale. Conclusion: Robotic therapy has emerged as a promising and effective intervention in post-stroke rehabilitation. It offers precise, personalized treatment by enabling repetitive, task-specific movements that improve motor function. Additionally, real-time feedback enhances patient motivation and optimizes movement quality. When integrated with conventional rehabilitation techniques, robotic therapy has the potential to increase treatment accessibility, particularly in resource-limited settings, making it an essential tool in modern neurological care.